Peningkatan Badan Usaha Milik Desa Melalui Booklet Potensi Usaha di Desa Mekarsari, Sumedang Jawa Barat: Indonesia - Kadiyono, Anissa Lestari; Kantate, Gloria; Zahra, Marsanda; Maksum, M. Farras; Susanto, Wahyu; Meilina, Ivana; Pasha, Ragnar; Tasmira, Alya (UII, 2025)
Mekarsari Village is one of the villages with diverse business potential. The products produced range from food and bamboo handicrafts to clothing convection. However, the problem is that the community has yet to be able to market their business products widely. This research aims to increase the role of Village-Owned Enterprises (BUMDes) by creating a booklet containing business potential in Mekarsari Village. The method used in this research is in-situ observation of villagers and surveys of other hamlets to find out the livelihoods of people in the surrounding area. After conducting field observations, data was collected through qualitative interviews with Mekarsari villagers who work as producers of clothing, shelter, and food. The results showed that booklet making is an effective means to realize the marketing of processed products produced in Mekarsari Village. In addition to being a promotional medium, the booklet also shapes positive perceptions and builds mutual support for sustainable economic development in Mekarsari Village.